(untitled) (Research, Society and Development, 2023)
Leprosy, a transmissible infectious disease whose agent, Mycobacterium leprae, causes skin lesions and neuropathies. Because it is endemic in Brazil, the Ministries of Health and Education established a specific agenda for prevention and health promotion in public schools through the Health at School Program. This experience report was able to develop health education activities on leprosy, associated with the active search for spots on the skin of students and family members of the Municipal Elementary School and provide a pedagogical instrument on leprosy control for Community Health Agents of the Riacho Doce Family Health Strategy. The methodology followed the Situational Strategic Planning, for the elaboration of the operations treated for the production of the early detection rate of leprosy, combating the information about the disease and the abandonment of the active search. The presentation of a theatrical play proved to be pedagogically efficient in passing on knowledge about leprosy prevention to Elementary School students; adaptation of the protection sheet adopted by the Ministry of Health, facilitating the active search process. The simplified booklet represents a learning tool for Community Health Agents. The pathogenic results show the importance of early diagnosis as well as evidenced the need for emergence and systematization of health promotion activities, greater interaction between the health of the Community, families and work teams. The integration between Education and Health Institutions proved to be effective, both in the practice of students and in the involvement of actors in the territory.